Pernikahan Beda Agama Berdasarkan Hukum Islam dan Undang-undang Nomor 1 Tahun 1974 Tentang Perkawinan (Analisis Penetapan No. 42/Pdt.p/2014/PN.Unr) - Syaddan Dintara Lubis (ARBITER: Jurnal Ilmiah Magister Hukum, 2023)
In practice, interfaith marriages are declared valid if they have received a permit decision from the court so that they can be registered. Even though in Law no. 1 of 1974, interfaith marriages are still experiencing a legal vacuum. In the event that the registration of marriages in interfaith marriages cannot be carried out because they are not in accordance with Article 2 paragraph (1) of Law No. 1 of 1974, but if accompanied by a permit decision from the court, interfaith marriages can be registered even though they are contrary to religious law, customary law and UU no. 1 of 1974. Consideration of freedom to embrace religion as a human right contained in the 1945 Constitution, in fact the principle of human rights returns the marriage law to the religious law adhered to by each religion. This study uses a normative study with a decision analysis approach No. 42/Pdt.P/2014/Unr based on the considerations of Islamic law and Law Number 1 of 1974. The aim is legal certainty in interfaith marriages and examines judges' considerations in granting permits for interfaith marriages. The results of the study show that normatively it is prohibited because it is not in accordance with Law No. 1 of 1974, if marriage is legalized because of a court decision to be registered so that it is considered valid, then it can weaken the position of Islamic law as a source of law for adherents of Islam, in principle the law Marriage refers to religious law.